2014
DOI: 10.1002/2013gl058476
|View full text |Cite
|
Sign up to set email alerts
|

Low wave speed zones in the crust beneath SE Tibet revealed by ambient noise adjoint tomography

Abstract: We present a refined 3D crustal model beneath SE Tibet from ambient noise adjoint tomography. Different from ray-theory-based tomography, adjoint tomography in this study incorporates a spectral-element method (SEM) and takes empirical Green's functions (EGFs) of Rayleigh waves from ambient noise interferometry as the direct observation. The frequency-dependent traveltime misfits between SEM synthetic Green's functions and EGFs are minimized with a preconditioned conjugate gradient method, meanwhile the 3D mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 34 publications
(43 reference statements)
3
101
0
Order By: Relevance
“…In our previous work (Sun et al, 2014), two intra-crustal LVZs were imaged along a ∼25 • N latitude profile in SE Tibet through joint inversion of Rayleigh wave dispersion and receiver functions. Using ambient-noise adjoint tomography, Chen et al (2014) also observed disconnected channels of LVZs in SE Tibet. Fig.…”
Section: Implications For the Deformation Of Se Tibetmentioning
confidence: 94%
“…In our previous work (Sun et al, 2014), two intra-crustal LVZs were imaged along a ∼25 • N latitude profile in SE Tibet through joint inversion of Rayleigh wave dispersion and receiver functions. Using ambient-noise adjoint tomography, Chen et al (2014) also observed disconnected channels of LVZs in SE Tibet. Fig.…”
Section: Implications For the Deformation Of Se Tibetmentioning
confidence: 94%
“…The cross correlations of ambient seismic noise have become indispensable in seismic tomography (e.g., Chen et al, ; de Ridder et al, ; Fang et al, ; Green et al, ; Lin et al, ; Mordret et al, ; Nakata et al, ; Nishida, Kawakatsu & Obara, ; Saygin & Kennett, ; Stehly et al, ; Yang et al, ; Zheng et al, ) and studies of attenuation and elastic (de) amplification (Bowden et al, ; Denolle et al, ; Harmon et al, ; Prieto et al, ). Current techniques are based on the assumption that cross correlations of the ambient seismic field converge to approximate interreceiver Green's functions (Boschi & Weemstra, ).…”
Section: Introductionmentioning
confidence: 99%
“…The shape of the Gaussian function is determined by half widths in the horizontal and vertical directions, σ x and σ z . Following Chen et al (2014), the optimal step length can be determined by minimizing the misfit calculated from a subset of virtual sources selected from a large number of stations. These two widths are reduced as the model improves.…”
Section: Inversion Strategymentioning
confidence: 99%
“…This results in seismic images with less accurate anomaly patterns and amplitudes. Based on these advances, Chen et al (2014) and Liu et al (2017) proposed ambient noise adjoint tomography for 3-D crustal structures by matching the empirical Green function (EGF) and synthetic Green function (SGF) calculated based on SEM. Utilizing these seismic wave simulations, adjoint-state methods can efficiently incorporate the full nonlinearity of wave propagation in iterative seismic inversions (e.g., Bozdag et al, 2016;Chen et al, 2015Chen et al, , 2017Fichtner & Villaseñor, 2015;Fichtner et al, 2009Fichtner et al, , 2010Liu & Gu, 2012;Liu & Tromp, 2006Tape et al, 2009Tape et al, , 2010Tromp et al, 2005;Zhu et al, 2012;Zhu & Tromp, 2013, Zhu et al, 2015.…”
Section: Introductionmentioning
confidence: 99%